Interaction of parasitoids associated with fruit flies attacking star fruit (Averrhoa carambolae) in Denpasar City, Bali Province, Indonesia. Issue 1 (1st February 2022) - Yuliadhi, K A; Susila, I W; Supartha, I W; Sultan, A; Yudha, I K W; Utama, I W E K; Wiradana, P A
Abstract: Star fruit (Averrhoa carambola) is a fruit plant that has a high consumption rate, especially in the Central/South America and Asia-Pacific regions including Indonesia. The fruit fly, Bactrocera spp. become a major pest on star fruit commodities in Indonesia which can harm quantity and quality which in turn hampers export activities. The aims of this study was to identify the type of pest, the level of attack, and the type of parasitoid associated with star fruit flies in the Denpasar City area. Fruit samples were collected using a purposive sampling method, namely collecting symptomatic fruit planted in four sub-districts in Denpasar City. Identification was carried out on the types of fruit flies and parasitoids that emerged after the rearing period. The percentage of fruit damage and the degree of parasitization was also determined. The fruit flies identified were Bactrocera carambolae and B. dorsalis and two parasitoids, namely Fopius arisanus and Diachasmimorpha longicaudata. The percentage (%) of fruit damage was 83.10%. The interaction that occurs between the fruit fly population and the level of damage is also very close. In all observation sites in Denpasar City, the parasitization rate of F. arisanus was higher than that of D. longicaudata. Our findings indicate that fruit flies are one of the main causes of star fruit damage in Denpasar City and should be integrated into a more comprehensive Integrated Pest Management (IPM) program by the relevant authorities.